Red, white & true blue Mallory - Friedman, Laurie B., 1964-; Kalis, Jennifer (Minneapolis, MN : Carolrhoda Books, 2009)
Mallory's journal of her fourth-grade trip to Washington, D.C., reveals how much fun she has, despite a loose tooth, being upset with her best friend, Mary Ann, and getting separated from her class in a museum.
Horn Book.
School Library Journal.
Horn Book, October 2009.
School Library Journal, September 2009.
5.2
3-6
Keywords: Best friends -- Juvenile fiction; Diaries -- Juvenile fiction; Friendship -- Juvenile fiction; School field trips -- Juvenile fiction; Tourism -- Juvenile fiction; Best friends -- Fiction; Diaries -- Fiction; Friendship -- Fiction; School field trips -- Fiction; Tourism -- Fiction; Diaries -- Fiction; Field trips -- Fiction; Friendship -- Fiction; Travel -- Fiction; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction; Washington (D.C.) -- Fiction